Immunization studies with attenuated strains of Bacillus anthracis. - Ivins, B E (1986)
Live, attenuated strains of Bacillus anthracis lacking either the capsule plasmid pXO2, the toxin plasmid pXO1, or both were tested for their efficacy as vaccines against intravenous challenge with anthrax toxin in Fischer 344 rats and against aerosol or intramuscular challenge with virulent anthrax spores in Hartley guinea pigs. Animals immunized with toxigenic, nonencapsulated (pXO1+, pXO2-) strains survived toxin and spore challenge and demonstrated postimmunization antibody titers to the three components of anthrax toxin (protective antigen, lethal factor, and edema factor). Immunization with two nontoxigenic, encapsulated (pXO1-, pXO2+), Pasteur vaccine strains neither provided protection nor elicited titers to any of the toxin components. Therefore, to immunize successfully against anthrax toxin or spore challenge, attenuated, live strains of B. anthracis must produce the toxin components specified by the pXO1 plasmid.